Outcome of AL amyloidosis after high-dose melphalan and autologous stem cell transplantation: long-term results in a series of 421 patients - Cibeira, Maria Teresa (American Society of Hematology, 2011)
Previous studies have suggested that, in patients with AL amyloidosis treated with high-dose melphalan and autologous stem-cell transplantation (HDM/SCT), the greatest benefit is seen in those patients achieving a hematologic complete response (CR). We analyzed a series of 421 consecutive patients treated with HDM/SCT at a single referral center and compared outcomes for patients with and without CR. Treatment-related mortality was 11.4% overall (5.6% in the last 5 years). By intention-to-treat analysis, the CR rate was 34% and the median event-free survival (EFS) and overall survival (OS) were 2.6 and 6.3 years, respectively. Eighty-one patients died within the first year after HDM/SCT and were not evaluable for hematologic and organ response. Of 340 evaluable patients, 43% achieved CR and 78% of them experienced an organ response. For CR patients, median EFS and OS were 8.3 and 13.2 years, respectively. Among the 195 patients who did not obtain CR, 52% achieved an organ response, and their median EFS and OS were 2 and 5.9 years, respectively. Thus, treatment of selected AL patients with HDM/SCT resulted in a high organ response rate and long OS, even for those patients who did not achieve CR.